Association of Neonate’s Birth Weight with Material Weight Gain during Pregnancy - Syeda Surayya Jabeen; Shazia Iffet; Umber Imtiaz; Faria Mumtaz; Bushra Sultana; Ayesha Arif (Journal of Rawalpindi Medical College)
Objective: To establish a relationship between maternal weight gain during pregnancy and a newborn’s birth weight.